2013
DOI: 10.1016/j.jbiomech.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and classification of regional peak plantar pressures of diabetic feet

Abstract: High plantar pressures have been associated with foot ulceration in people with diabetes, who can experience loss of protective sensation due to peripheral neuropathy. Therefore, characterization of elevated plantar pressure distributions can provide a means of identifying diabetic patients at potential risk of foot ulceration. Plantar pressure distribution classification can also be used to determine suitable preventive interventions, such as the provision of an appropriately designed insole. In the past, emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 32 publications
(37 reference statements)
4
43
0
Order By: Relevance
“…The causes could be related to the fact that diabetic individuals, especially those with greater levels of complications, present a shorter stride length and a longer cycle time when compared with healthy subjects, thus agreeing with other studies 4,20,22 . Furthermore, with respect to velocity, it was noted that the lower values found in the NG and NVG groups were inversely related to the double support/single support ratio.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The causes could be related to the fact that diabetic individuals, especially those with greater levels of complications, present a shorter stride length and a longer cycle time when compared with healthy subjects, thus agreeing with other studies 4,20,22 . Furthermore, with respect to velocity, it was noted that the lower values found in the NG and NVG groups were inversely related to the double support/single support ratio.…”
Section: Discussionsupporting
confidence: 90%
“…This finding could be one possible explanation for the fact that increases in peak plantar pressure 10 , associated with other factors, precede the appearance of ulcerations and foot amputations in this population 20,21 consistent with the findings of this study, which indicated that points receiving abusive overload to structures frequently bore signs of existing injuries.…”
Section: Discussionsupporting
confidence: 89%
“…They have considered other predictors for diabetes detection, but the drawback is that although particularly the case for small data needs an external validation before applying a model. Bennetts C.J et al [5] intended for exploited a relationship of the diabetes dataset for classification capability. Like many researchers, Bennetts C.J et al [5] tried to employ the data mining approaches in the biological organization for discovering new knowledge which assists to help a medical doctor for accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Bennetts C.J et al [5] intended for exploited a relationship of the diabetes dataset for classification capability. Like many researchers, Bennetts C.J et al [5] tried to employ the data mining approaches in the biological organization for discovering new knowledge which assists to help a medical doctor for accurate diagnosis. A brief overview is provided by Tomar et al [6] of these methods and their advantages and drawback.…”
Section: Introductionmentioning
confidence: 99%
“…Gait conditions, associated to Diabetes Mellitus (DM), are most frequently assessed with plantar pressure measurement (PPM) equipment because elevated pressures are considered as a major risk factor of ulceration [1,2]. The aim of this study was to identify groups with similar forefoot loading patterns and to verify if specific groups of diabetic patients (PwDM) could be isolated from non-diabetic persons (Ctrl).…”
Section: Introduction and Aimmentioning
confidence: 99%